1989
DOI: 10.1002/asna.2113100407
|View full text |Cite
|
Sign up to set email alerts
|

uvby photometry of open clusters

Abstract: Fur insgesamt 40 Stern im Gebiet des verfarbten offenen Haufens NGC 6871 erhielten wir eine uubv Photometric. 21 dieser Sterne klassifizierten definitely as members. From the photometric results we derived 1.2 x IO' years as the cluster age. 2440 pc as its distance. and (E(h --y ) ) = 0.348 mag as mean reddening of the cluster. From the scatter around this mean colour excess and the deviation of a subgroup of stars by more than twice the standard deviation a varible intracluster reddening in order of 0.1 mag i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 19 publications
6
21
0
Order By: Relevance
“…In the color-magnitude diagram this star lies in the cold giant region ( T eff = 5800 K [12]), or is a strongly reddened object of still greater luminosity embedded in a dense gas-dust cloud. It was found to be of spectral type of G2 in [12], where it was suggested that the star is not a member of the cluster. Our observations also indicate that HD 277630 is most likely not a member of the cluster.…”
Section: Hα α α α α Line Profiles Of B and Be Stars In The Clustersmentioning
confidence: 98%
See 4 more Smart Citations
“…In the color-magnitude diagram this star lies in the cold giant region ( T eff = 5800 K [12]), or is a strongly reddened object of still greater luminosity embedded in a dense gas-dust cloud. It was found to be of spectral type of G2 in [12], where it was suggested that the star is not a member of the cluster. Our observations also indicate that HD 277630 is most likely not a member of the cluster.…”
Section: Hα α α α α Line Profiles Of B and Be Stars In The Clustersmentioning
confidence: 98%
“…Later [12], a study of 21 stars in the cluster yielded an average of DM = 11 m .94 ± 0 m .08, which corresponds to a distance of 2440±100 pc. Finally, the distance modulus has been estimated [13] to be 11 m .65 ± 0 m .07.…”
Section: General Characteristics Of the Clustersmentioning
confidence: 99%
See 3 more Smart Citations